Pelibatan Anak Dalam Pemilihan Umum - Cindy Agnesia Ratmala; Elsa Rina Maya Toule; Erwin Ubwarin (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The involvement of children in political campaign activities is a phenomenon that recurs every 5 years or every campaign cycle. Involving children in political campaign activities is not the right action because children have the right to be free from the abuse of political activities.Purposes of the Research: This writing aims to analyze the forms of protection where children are involved in the General Election and to analyze whether political parties can be held responsible for the crime if they involve children in general elections.Methods of the Research: The research method in this writing uses a normative juridical research type. The research approach used is a statutory approach and a conceptual approach. The procedure for collecting legal materials uses library research, as well as legal material analysis techniques in this study using qualitative analysis techniques.Results of the Research: The results obtained are that a form of legal protection for children involved in the election is a form of preventive legal protection and a form of repressive legal protection. Then regarding criminal responsibility, one of the conditions for the formation of political parties is that political parties must be registered with the Ministry to become a legal entity and obtain ratification as a legal entity. Thus political parties that involve children in general elections can be held responsible for the crime.